Facial alveolar bone wall width- a cone-beam computed tomography study in Asians - Zekry, A.; Ren, W.; Chau, Anson; Lang, N. (Wiley-Blackwell Publishing, Inc., 2014)
Background: The width of the facial alveolar bone wall is crucial for long-term successful esthetic outcomes of implants immediately placed into extraction sockets. A threshold of 2 mm is recommended to minimize buccal vertical bone resorption. Aim: To assess the width of the facial alveolar bone wall using cone-beam computed tomography images (CBCT). Material and methods: Retrospective CBCT images were acquired from a representative sample of Asians using the i-CAT® classic system with a 0.4-mm voxel size. At random, 200 CBCT images were selected according to predefined criteria. The DICOM file was imported into the i-CAT Vision® software. In the panoramic screen, the middle of each tooth was selected, and in the sagittal window, the middle cross section was selected for performing the measurements using a computer. The vertical distance from the alveolar crest (BC) – cemento-enamel junction (CEJ) was measured. The width of the facial alveolar bone wall was measured at three locations: 1, 3, and 5 mm apical to BC. Descriptive statistics, frequency analyses, and multi-level comparisons were performed.Results: The sample consisted of 74 men and 126 women (mean age of 37.2 years; range 17–82years). A total of 3618 teeth were assessed. There was no significant difference between the values of right and left sides, or between genders. However, statistically significant differences were observed between age groups at all levels. The distance from CEJ to BC varied from 0.4 to 4 mm, with an overall tendency to increase with age. The mean width of the facial alveolar bone wall at anterior teeth was 0.9 mm and increased toward posterior regions. Rarely, a width of 2 mm was yielded (0.6–1.8% for anterior teeth, 0.7–30.8% for posterior teeth). At a 5-mm distance from BC, minimal widths of facial alveolar bone were identified for the anterior teeth. The frequency of dehiscence ranged from 9.9% to 51.6% for anterior and 3.1% to 53.6% for posterior teeth, respectively. Conclusion: A thin facial alveolar bone wall was usually present in both jaws. Hence, for most patients, adjunctive bone augmentation may be needed when installing implants in areas of esthetic concern.